Reflection on research trends with the theme of archives management in the range of 3 decades (1994-2024): A bibliometric analysis - Avidiansyah, Zulfa (D3 Perpustakaan Fakultas Vokasi Universitas Airlangga, 2025)
Background of the study: Archives management is a concept needed in the current era, as its implementation has become commonplace in many places. Supported by the development of information technology, it has affected the technical process and research related to archives. Purpose: This study aims to provide an overview of research on archives management over the last 3 decades to determine whether it remains widely discussed. Method: This research uses a quantitative bibliometric approach, retrieving data from the Scopus database on archives management between 1994 and 2024. Findings: This research shows that archives management over the last 3 decades has maintained strong network ties across several topics. Archives management still has a density that provides quite a lot of research references. Reflections on the division of three decades show significant differences in their progress. Conclusion: Countries such as the United States, the United Kingdom, China, South Korea, and Australia still have substantial network strength in archival management research. As for future implications, it can be seen that current archives management remains relevant, with the note that, along with trending topics such as information management, blockchain, archives management systems, and quality control, these topics can be incorporated into updating archives management. However, it remains to be seen and warrants further investigation, especially when using filters and entering more keywords, which may produce different results.